Adaptive market hypothesis: Evidence from the Vietnamese stock market - Phan Tran Trung Dzung; Hung Pham Quang (Journal of Risk and Financial Management, 2019)
This paper aims to test the adaptive market hypothesis in the two main Vietnamese stock exchanges, namely Ho Chi Minh City Stock Exchange (HSX) and Hanoi Stock Exchange (HNX), by measuring the relationship between current stock returns and historical stock returns. In particular, the tests employed are the automatic variance ratio test ("AVR"), the automatic portmanteau test ("AP"), the generalized spectral test ("GS"), and the time-varying autoregressive (TV-AR) approach. The empirical results validate the adaptive market hypothesis in the Vietnamese stock market. Furthermore, the results suggest that the evolution of HSX has served as an important factor of the adaptive market hypothesis.
Keywords: 330; adaptive market hypothesis; market efficiency; autocorrelation